2016
DOI: 10.1175/wcas-d-15-0071.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Education and Knowledge among Nigerian University Graduates

Abstract: The introduction of climate change studies in universities has a fundamental role in helping the general public, especially the next generations, to recognize the global challenges of climate change and to find ways of adapting to the changing climate. This study examined the level of climate change education and perception of Nigerian university graduates. A mixed method approach was used to obtain data relating to perceptions, understanding, and level at which climate change has been taught in Nigerian unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…This implies that university students or those who have a higher level of education are more likely to have an impact on climate change (Eurobarometer 2001 ). This was supported by Ayanlade ( 2016 ) who found that a large number of graduates from Nigerian universities have knowledge about climate change and they developed awareness of climate change through different channels.…”
Section: Introductionmentioning
confidence: 89%
“…This implies that university students or those who have a higher level of education are more likely to have an impact on climate change (Eurobarometer 2001 ). This was supported by Ayanlade ( 2016 ) who found that a large number of graduates from Nigerian universities have knowledge about climate change and they developed awareness of climate change through different channels.…”
Section: Introductionmentioning
confidence: 89%
“…Pandve and Raut [22], examined climate change knowledge among medical students, Rahman et al [23] studied climate change awareness among high school students, Parant et al [24] inquired into how to raise students' awareness on climate change, and Frejie [25] assessed global warming awareness among university of Bahrain science students. Ayanlade and Jegede [26] studied climate change education and knowledge among university graduates in Nigeria whilst Buggy and McGlynn [27] studied climate change awareness among Tanzania's second-level education system. Whilst these studies present insights about students' knowledge of climate change, key issues such as involving knowledge on indirect causes (such as meat consumption) and effects (such as conflicts and gender inequalities) of climate change were not explored.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while some KAP studies report significant levels of general (including household/layman) awareness, knowledge, and understanding of climate change issues (Hope 2016 ; Falaye and Okwilagwe 2016 ; CIMC 2012 ), others indicate high levels of awareness but low understanding of climate change. Studies in Nigeria by Oruonye ( 2011 ) among students of tertiary institutions and by Ayanlade and Olusolape Jegede ( 2016 ) among post tertiary education youth groups also follow this pattern.…”
Section: Literature Review: Migrant Remittances As Sources Of Climate Change Adaptation Fundingmentioning
confidence: 73%